Program Pembelajaran Agama Islam pada Lembaga Pendidikan Umum - Rinnanik, Rinnanik (Institut Agama Islam Negeri (IAIN) Metro, 2016)
This article discusses the role of Islamic education (PAI) in the form of strong values. PAI learning program in environmental public education institutions aims to embody the IMTAK embodied in religious program operates on the implementation of Islamic religious education either intrakurikuler or extracurricular activities that are improving the aspect of cognitive, affective and psychomotor practice guidance in the form of worship, study and lectures integrated, social service, religious and race others. As for some effort in overcoming the obstacles of the program is the use of the methods of delivery, coaching for students with minimal knowledge of religion, good cooperation between all parties and involve students directly in any religious activities.